Development of Automatic Hydroponic Plant Watering Based Arduino Microcontroller (Proksima, 2023)
This paper aims to develop a design for an automatic hydroponic plant nutrient sprinkler. This plant watering device used an Arduino Mega 2560 microcontroller as the interface and an LCD (Liquid Cristal Display) as a display to indicate nutrient levels. The device design deployed a time system set using an Arduino microcontroller and RTC (Real Time Clock) based watering time settings. The development of this automatic nutrient watering device was equipped with a TDS (Total Dissolve Solid) sensor, which reads the value of the nutrient solution content in the water. The LCD displayed monitoring system performance and the relay functions to turn on and off the water pump connected to the hydroponic media watering pipe installation. The benefits of the device can save time and energy. Therefore, the device is more efficient than the manual watering system.